마스크 착용 중 외상에 의해 발생한 Paenibacillus timonensis 각막염 1예 - Junwoo Lee; Jaehwan Choi; Kiyoung Kim; Min Seok Kang (검안 및 콘택트렌즈 학회지, 24(2), 2025)
목적: Paenibacillus timonensis 에 의한 각막염 1예를 경험하여 이를 보고한다. 증례요약: 41세 남자 환자가 마스크의 코 고정 철사에 좌안을 찔린 후 발생한 통증과 시력 저하를 주소로 내원하였다. 환자는 14년전부터 인슐린으로 조절 중인 당뇨 외에 다른 특이 병력은 없었다. 최대교정시력은 우안 20/20, 좌안 20/50이었으며, 세극등현미경검사에서 좌안에서 각막 침윤, 상피결손 및 각막 부종 소견과 함께 경미한 전방 염증이 관찰되었다. 경험적 항생제 치료로 moxifloxacin 0.5% 점안액을 매 3시간마다 점안하였다. 각막 병변을 찰과하여 실시한 배양검사 결과 P. timonensis가 동정되어 2.5% vancomycin 점안액을 추가로 사용하였다. 14일 후 각막 기질 침윤과 부종이 호전되며, 최대교정시력은 20/20으로 회복되는 것을 확인하였다. 1개월 후 상피하 혼탁을 남기고 각막염은 치유되었다. 결론: 마스크 착용 중 발생한 외상으로 인해 각막 침윤 및 혼탁이 관찰된 각막염 환자에서 국내외에서 보고된 적 없는 P. timonensis가원인균으로 동정되었기에 이를 보고한다. Purpose: To report a case of keratitis caused by Paenibacillus timonensis. Case summary: A 41-year-old male presented with pain and decreased vision in his left eye after being injured by the nose wire of a mask. He had a 14-year history of insulin-controlled diabetes mellitus but no other significant medical history. His best-corrected visual acuity (BCVA) was 20/20 for the right eye and 20/50 for the left eye. Slit-lamp examination revealed corneal infiltration, epithelial defects, corneal edema, and mild anterior chamber inflammation in the left eye. Empirical therapy with moxifloxacin 0.5% eye drops was initiated and administered every 3 hours. Corneal scraping for culture identified P. timonensis as the causative pathogen, and fortified vancomycin (2.5% eye drops) was added to the treatment regimen. The corneal stromal infiltration and edema resolved, and BCVA improved to 20/20 at 14 days after the initial treatment. The keratitis resolved with residual subepithelial corneal opacities at 1 month after treatment. Conclusions: This is the first reported case of P. timonensis keratitis in a patient with corneal trauma from a mask nose wire that resulted in corneal infiltration and opacity. KCI Citation Count: 0